Forests and sustainability - Bulkan, J.; Hajjar, R.; Hardcastle, P.; Assembe-Mvondo, Samuel; Eba'a Atyi, R.; Humphreys, D.; Maryudi, A. (IUFRO, 2010)
International forest governance has developed and evolved as concern for sustaining forests grew beyond the local level, culminating thus far in numerous institutions at the global level, each of which claims some mandate over various aspects of forest or forest-related policy. This situation can be understood as a result of the evolution of conceptualisations of what sustaining all forest values entails, which itself is the result, at least in part, of both shifting international interests and the relative dominance of various forest values in the different institutions. This chapter explores conceptualisations of forest sustainability as manifested in some of the key global instruments existing today and proposes reasons why these have not yet succeeded in achieving the overall goal of sustaining the world’s forests.